2012
DOI: 10.1371/journal.pone.0037263
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Temperate Bacteriophage Carriage in Clostridium difficile 027 Strains

Abstract: BackgroundThe hypervirulent Clostridium difficile ribotype 027 can be classified into subtypes, but it unknown if these differ in terms of severity of C. difficile infection (CDI). Genomic studies of C. difficile 027 strains have established that they are rich in mobile genetic elements including prophages. This study combined physiological studies, electron microscopy analysis and molecular biology to determine the potential role of temperate bacteriophages in disease and diversity of C. difficile 027.Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 38 publications
7
51
0
Order By: Relevance
“…It appears that these particles are widespread among the species. In addition, a recent study involving a collection of ribotype 027 C. difficile isolates found that they produced phage tail-like particles that morphologically resembled diffocins similar to our 027 diffocin producer, CD16 (27). Further work is needed to determine if diffocins from all 027 strains have identical killing spectra.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It appears that these particles are widespread among the species. In addition, a recent study involving a collection of ribotype 027 C. difficile isolates found that they produced phage tail-like particles that morphologically resembled diffocins similar to our 027 diffocin producer, CD16 (27). Further work is needed to determine if diffocins from all 027 strains have identical killing spectra.…”
Section: Discussionmentioning
confidence: 92%
“…difficile strains produce R-type bacteriocins. After exposure to mitomycin C, many strains of C. difficile have been found by electron microscopy to produce particles with phage tail-like morphology (9,27,32) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We were able to further propagate them to high titers and characterize them by TEM, PFGE, restriction profiling, and host range analysis. Although several prophages have been induced from clinical and environmental C. difficile isolates (17)(18)(19)(20)(21), there is a dearth of genomic and functional data on this group of phages and one main reason for that is the lack of suitable propagating hosts and conditions, which are essential for further characterization. It is also worth mentioning that, to our knowledge, strictly lytic (i.e., virulent) phages in- …”
Section: Discussionmentioning
confidence: 99%
“…Several putative prophages can be identified by bioinformatic analyses of C. difficile whole-genome sequences available in public repositories. Several prophages and phage tail-like particles have also been induced from C. difficile lysogens by using UV, mitomycin C, and other antibiotics, and some of these phages have been partially characterized by electron microscopy, PFGE, and restriction profiling (17)(18)(19)(20)(21)(22). Most phages are members of the Myoviridae family, i.e., phages with nonflexible and contractile tails, whereas very few are members of the Siphoviridae family, i.e., phages with long, flexible, and noncontractile tails (23).…”
mentioning
confidence: 99%
“…All ribotypes, except R076, were clinical samples isolated from stool specimens collected from patients infected with C. difficile at the UHL Leicester hospitals (in descending order of number of cases detected). All cultures were isolated in the Department of Infection, Immunity, and Inflammation at the University of Leicester using standard procedures (Nale et al 2012). Ribotypes were determined according to standard protocols (Indra et al 2008) with reference to the strains categorized as part of the C. difficile ribotyping network (Fawley and Wilcox, pers comm.).…”
Section: Growth and Maintenance Of Microorganismsmentioning
confidence: 99%